Two-phase flow and heat transfer in reflux thermosyphons - Smith, Kate (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2016)
Improved cooling technologies are becoming necessary in electronic applications, specifically Radio Frequency Power Amplifiers (RFPA) installed in tower-top Remote Radioheads (RRH). Current methods of cooling are becoming inadequate as heightened service demands increase heat generation. The hardware is also subject to thermal cycling which can impact long-term reliability and function. With this in mind, the objectives of this study involve the design and characterisation of a small dimension thermosyphon suitable for use as an RFPA cooling solution and, ultimately, thermal management system. The performance of small-scale (Di ~ 10 mm) thermosyphons was determined in terms of both the rate of heat transfer and the fluid dynamics. The counter-current flow of the liquid and vapour phases in small-scale thermosyphons resulted in substantial interfacial forces that can lead to rapid deterioration of the rate of heat transfer. With small dimensions there is an additional restriction on the flow due to confinement of the vapour during evaporation, which can significantly affect the two-phase flow regimes. An initial feasibility study was performed to assess the capability of a two-phase thermosyphon in this particular application, using water as the working fluid. To mimic the operating conditions within the RRH, the condenser section of the thermosyphon was cooled by natural convection to ambient conditions. High watt density ceramic heaters were used as the heat source to replicate both the size and power output of the RFPA. The investigation of thermosyphon performance involved varying the fill volume of working fluid and installing various bend angles in the thermosyphon geometry. It was found that the thermosyphon could provide adequate cooling for the required application. The results highlighted the benefits of using bends in the thermosyphon geometry of a small-scale thermosyphon to reduce the liquid-vapour interfacial forces that can lead to deterioration of the heat transfer within the device. The vertical thermosyphon exhibited oscillatory, geyser boiling behaviour which deviated from the conventional boiling mechanisms described for thermosyphons: nucleate pool boiling and falling film condensation. The oscillatory boiling behaviour of small dimension thermosyphons was investigated by designing and constructing a fully transparent thermosyphon. Synchronised flow visualisation via high-speed imaging and thermal measurements enabled an interlinked study of the flow regimes and heat transfer. Three working fluids were employed to assess the performance with varied thermophysical properties. The observed flow regimes could be characterised in terms of the degree of confinement and rate of vapour production. Flow pattern maps were developed which could guide future small dimension thermosyphon design to avoid the geyser boiling regime, a result of a combination of both high levels of confinement and vapour production. The rate of heat transfer associated with each flow regime highlighted the flow regimes that were most conducive to high rates of heat transfer, mainly churn flow. Finally, an augmentation study of the flow regimes and heat transfer was carried out using electrohydrodynamics (EHD). This study outlined the potential opportunity for smart control of the heat transfer within thermosyphons. Both heat transfer enhancement and deterioration were observed, depending on the initial, free-field flow regime. The response of the system to EHD was also fast and reversible. In conclusion, a deep understanding of the flow regimes and associated heat transfer has been gained through analysis of the dominant forces in two-phase flow in small diameter thermosyphons. A novel thermosyphon design with complex geometry was developed providing a viable cooling solution for electronic applications. Further to this, a transparent test section was developed to characterise flow regimes and heat transfer in small dimension thermosyphons with the additional capability of EHD flow augmentation. This study highlighted the possibility of advanced thermosyphon cooling technologies with the prospect of high thermal performance and intelligent operation.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin